2012
DOI: 10.1080/00028487.2012.681102
|View full text |Cite
|
Sign up to set email alerts
|

Brook Trout Movement in Response to Temperature, Flow, and Thermal Refugia within a Complex Appalachian Riverscape

Abstract: We quantified movements of brook trout Salvelinus fontinalis and brown trout Salmo trutta in a complex riverscape characterized by a large, open‐canopy main stem and a small, closed‐canopy tributary in eastern West Virginia, USA. Our objectives were to quantify the overall rate of trout movement and relate movement behaviors to variation in streamflow, water temperature, and access to coldwater refugia. The study area experienced extremely high seasonal, yearly, and among‐stream variability in water temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
168
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(178 citation statements)
references
References 78 publications
8
168
1
Order By: Relevance
“…In a recent study, Kanno et al (2013) found that half of the surviving offspring of adult Brook Trout from a given stream were spawned in the stream's tributaries. These results support previous studies (Petty et al 2005(Petty et al , 2012 that have highlighted the importance of small tributaries for the persistence of Brook Trout populations and thus the necessity of maintaining genetic connectivity among main stems and tributaries for the proper conservation of Brook Trout and other salmonids with similar life cycles. As was illustrated in our study system, forest roads are generally built along main stems, leading to the installation of culverts near tributary mouths.…”
Section: Management Implications Of Culverts' Impacts On the Distribusupporting
confidence: 92%
“…In a recent study, Kanno et al (2013) found that half of the surviving offspring of adult Brook Trout from a given stream were spawned in the stream's tributaries. These results support previous studies (Petty et al 2005(Petty et al , 2012 that have highlighted the importance of small tributaries for the persistence of Brook Trout populations and thus the necessity of maintaining genetic connectivity among main stems and tributaries for the proper conservation of Brook Trout and other salmonids with similar life cycles. As was illustrated in our study system, forest roads are generally built along main stems, leading to the installation of culverts near tributary mouths.…”
Section: Management Implications Of Culverts' Impacts On the Distribusupporting
confidence: 92%
“…Previous research in this system suggests that brook trout inhabiting larger main stem sites may compete for thermal refugia during prolonged periods of warm and dry conditions [28]. During the spring, brook trout in the main stem may also compete for optimal growing habitat [64].…”
Section: Discussionmentioning
confidence: 92%
“…Gradients in environmental conditions such as temperature are particularly important for cold-water specialists like salmonids that require specific thermal ranges for optimal performance within a habitat [32][34]. Petty et al [28] observed high mobility in brook trout exposed to elevated thermal conditions within a large main stem habitat, while tributary residents showed less mobility, likely due to relatively lower thermal stress. Additionally, demographic rates of fish species (e.g., survival and birth rates) have been shown to differ based on whether fish were present in their core or peripheral distribution within the same watershed [27].…”
Section: Introductionmentioning
confidence: 99%
“…Habitat selection by Brook Trout has been studied in some areas within the species' native range (Baker et al 1996;Baird and Krueger 2003;Petty et al 2005Petty et al , 2012Mollenhauer et al 2013), and several studies have revealed the spatial and temporal dynamics of habitat selection by Brown Trout under differing flow regimes (Ayllón et al 2010(Ayllón et al , 2014. However, few studies have focused on quantifying habitat use by both Brook Trout and Brown Trout within the same time period and in the same geographic location (Baird et al 2006).…”
mentioning
confidence: 98%